2007
DOI: 10.1558/sols.v7i2.265
|View full text |Cite
|
Sign up to set email alerts
|

Linguistic attitudes in Aragon

Abstract: The study of the linguistic attitudes has been considered a key element when we pretend to guarantee the success of any proposal of treatment of the languages in the school. In spite of it, in the case of Aragon (Spain), where three languages are s p o ken along the terr i t o ry, the practical non-existence research in this way is only coherent with the lack of determination that the topic has been traditionally treaty. In this context, taking as a reference school children in Compulsory Secondary Education, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…However, around 5% of its population live in a narrow area bordering Catalonia in which Catalan has traditionally been the home language of its inhabitants and it is still widely spoken by the majority of them, albeit with very little appreciation of it in the public sphere. The results of that study showed that socio‐professional status did not affect attitudes towards Catalan, Spanish or even French but it did have a significant effect on attitudes towards English (Huguet & Lapresta, 2006), in the sense that higher status carried along more favourable attitudes to this language, thus highlighting the role of English as a social marker, supported and embraced by dominant socio‐economic elites, with the potential side effect of further increasing the divide between privileged and unprivileged elements in society.…”
Section: Attitudes To Englishmentioning
confidence: 97%
“…However, around 5% of its population live in a narrow area bordering Catalonia in which Catalan has traditionally been the home language of its inhabitants and it is still widely spoken by the majority of them, albeit with very little appreciation of it in the public sphere. The results of that study showed that socio‐professional status did not affect attitudes towards Catalan, Spanish or even French but it did have a significant effect on attitudes towards English (Huguet & Lapresta, 2006), in the sense that higher status carried along more favourable attitudes to this language, thus highlighting the role of English as a social marker, supported and embraced by dominant socio‐economic elites, with the potential side effect of further increasing the divide between privileged and unprivileged elements in society.…”
Section: Attitudes To Englishmentioning
confidence: 97%